Restaurant Noise: Levels and Temporal Characteristics. (September 2015) - To, W.M.; Chung, A.W.L.
Noise in restaurants affects diners and service employees. Normally, people will not eat alone. They would rather enjoy good food and drink with business partners, friends, and family in restaurants and unavoidably they talk happily and loudly. Speeches from other restaurant patrons, service employees, mingling with background music and noise from ventilation systems, will interfere with communication between a talker and listeners. This paper presents a territory-wide noise survey in Hong Kong restaurants and presents a mathematical model that describes the background noise level in restaurants. The measured noise levels show that restaurant noise ranged from 66.7 to 82.6 dBA with a mean value of 73.9 dBA (SD = 3.81 dBA) while the mathematical model illustrates that the background noise level in restaurants mainly depends on the occupancy density. The model was validated by another two sets of noise measurement data recorded in other restaurants. The time record of noise measurement shows that the variation of noise levels decreases when the occupancy density increases. People have to raise their voice effort to improve their speech intelligibility in a very noisy environment.